Switched-coupled-inductor DC/DC converters with high voltage conversion ratio. (8th October 2010) - Laird, Ian; Lu, Dylan Dah-Chuan; Agelidis, Vassilios G.
When a low voltage DC power source is used, a DC-DC converter with a high step-up voltage gain is required to raise the voltage to more applicable levels. This is typically achieved by using classical converters driven by pulse width modulation (PWM) waves with extremely high duty cycles. Although theoretically step-up converters can achieve an infinite gain as the duty cycle approaches unity, in reality the gain will peak due to losses in the converter. Increasing the duty cycle beyond this point will only degrade the voltage gain. A solution to this problem is to use a converter that will produce the desired gain at a smaller duty cycle. This paper proposes replacing the inductor in the classical boost converter with a switched-coupled-inductor (SCL) configuration in order to achieve high gains with moderate duty cycles. Mathematical analysis is presented along with selected experimental results to support the theoretical considerations.